Long-term follow-up of Janus-kinase inhibitor and novel active disease biomarker in juvenile dermatomyositis. (29th July 2022) - Huang, Baozhen; Wang, Xinning; Niu, Yanlin; Ding, Yuchuan; Wang, Xiaolei; Tan, Qingqing; Li, Yucong; Liu, Yuan; Chi, Ying; Wang, Yuan; Zhou, Zhixuan; Li, Jianguo
Abstract: Objective: To evaluate the use of Janus kinase inhibitor (JAKi) in treating JDM and develop cytokine biomarkers of active disease. Methods: This study involved a retrospective cohort study that evaluated JAKi in 101 JDM patients as well as a cross-sectional study of cytokines in 128 JDM patients and 30 controls between November 2017 and December 2021 in the Affiliated Children's Hospital of Capital Institute of Pediatrics (China). Results: During the median follow-up period of 19 months, 65.5% of the patients had improved rashes, and CAT-BM scores decreased. Overall, 39.6% of JDM patients eliminated glucocorticoids. Muscle strength was improved in all patients who had abnormal muscle strength before JAKi use. Patients and parents provided positive subjective reviews of JAKi, and no serious adverse events were reported. Potential side effects of JAKi included abnormal leukopoenia (14/95) and cough (16/83), which affected over 10% of the JDM patients. In the cytokine analysis, 12/34 cytokines were significantly elevated in active JDM patients. Compared with active JDM patients with multiple phenotypes, active JDM patients with only rashes demonstrated lower cytokine levels. Anti-NXP2-positive active patients had lower cytokine levels compared with those without positive anti-NXP2 antibodies. Among all increased cytokines, IL-1RA changed most dramatically, reaching over 793 times the mean of normal values. We developed a panel composed of six cytokines to differentiate active or stable status in our cohort (area under the curve = 0.8486, P < 0.05). Conclusion: The preliminary evidence suggested that JAKi is a relatively safe and effective alternative for JDM patients. Cytokine profiles could well reflect the inflammatory status of JDM patients.